Clinical Outcomes of Surgical Treatment for Piriformis Syndrome - Kakarash Asaad , Saywan (Hammurabi Journal of Medical Sciences, 2026)
Background: Piriformis Syndrome (PS) is an compressive neuropathy of sciatic nerve at the level of ischial tuberosity multiple factors are involved in this disorder including anatomical variation in the pathway of sciatic nerve through or near the pirifomis muscle and bipartite pirifomis. There are also other factors that may contribute to compression including muscle spasm, trauma and tumor. Objectives: this study aims to explore the clinical presentation, diagnostic challenges, and effective management approaches for PS. Materials and Methods: This single-center case series included consecutive patients diagnosed with PS and treated between January 2023 and May 2025. Inclusion criteria comprised a clinical diagnosis of PS during the study period, completion of both conservative and surgical treatments, and availability of MRI imaging. Data collection occurred after the completion of all clinical care, with the data subsequently organized and analyzed qualitatively. Results: This study included 10 patients diagnosed with PS, comprising 7 males (70%) and 3 females (30%), aged 22 to 46 years. 9 patients (90%) reported chronic buttock pain radiating down the leg. Diagnosis was established using the FAIR test and MRI. All patients were initially treated conservatively; however, symptoms did not improve, necessitating surgical intervention. Following operation, 8 patients (80%) achieved good to very good symptom relief. Conclusion: Identifying PS as a distinct clinical condition and applying a systematic diagnostic and treatment approach can lead to meaningful improvements in patient outcomes. Surgical treatment, informed by clinical assessment and imaging findings, may reduce morbidity and improve functional outcomes, especially in patients who do not respond to conservative therapy.